Issues of integrating GIS and mobile technologies in location-based services - Paliulionis, Viktoras (Geodesy and Cartography, 2012)
Location-based serviced (LBS) provide with information and services depending on the location of the user or mobile object. The services can be accessible through mobile phones, handheld computers, and other small portable devices. The application area of LBS encompasses tourist information, mobile commerce, emergency services, automated vehicle location, etc. They integrate GIS, Internet, wireless communication and positioning technologies. The goal of the paper is to survey the LBS types, geographic information system (GIS) and mobile information technologies, and present the general architecture of LBS systems. The presented architecture is based on the client-server model, with a GIS server as a principal component of the architecture. The visualisation of geographic data in such systems is studied by mobile cartography. Peculiarities of mobile cartography are related to specific features of mobile devices (small screen size and resolution, memory restrictions, etc.), and dynamic and adaptive nature of the map visualisation. Very few principles of mobile cartography are implemented into the practice up to now, so it is expedient to pursue a closer co-operation between cartographers, GIS specialists, mobile information technology specialists and other professionals to develop the methods in detail and put them into practice.Article in Lithuanian.GIS ir mobiliųjų technologijų integravimo lokalizuotųjų paslaugų sistemose ypatumaiSantrauka. Lokalizuotųjų paslaugų sistemos teikia informaciją ir kitokias paslaugas naudodamos duomenis apie mobiliojo objekto arba vartotojo buvimo vietą. Jų paslaugos pasiekiamos mobiliaisiais telefonais, delniniais kompiuteriais ir kitais mobiliaisiais įrenginiais. Lokalizuotosios paslaugos – tai pagalbos tarnybų paslaugos, mobilioji komercija, transporto priemonių stebėjimas, turizmo informacija ir kitų sričių paslaugos. Darbo tikslas yra ištirti lokalizuotųjų paslaugų tipus, joms teikti taikomas geografinės informacijos sistemų (GIS) ir mobiliąsias informacines technologijas bei pasiūlyti apibendrintąją tokių sistemų architektūrą. Pateiktoji architektūra grindžiama kliento – tarnybinės stoties modeliu, o bazinių paslaugų teikimo pagrindas yra GIS komponentas. Geografinių duomenų vizualizavimą tokiose sistemose nagrinėja vadinamoji mobilioji kartografija. Jos ypatumai yra susiję su mobiliųjų įrenginių ribojimais (mažas ekrano dydis, maža skiriamoji geba, atminties ribojimai ir pan.) bei su žemėlapio pateikimo dinamiškumo ir adaptyvumo reikalavimais. Mobiliosios kartografijos principams įgyvendinti turėtų glaudžiau bendradarbiauti kartografai, GIS specialistai, mobiliųjų informacinių technologijų ir kitų sričių specialistai.Raktažodžiai: GIS, lokalizuotųjų paslaugų sistema, mobilioji kartografija, GPS, programų sistemų architektūra.First published online: 03 Aug 2012